USING ARTIFICAL INTELLIGENCE TOOLS FOR RISK ASSESSMENT IN THE PROJECT MANAGEMENT FOR IT INDUSTRY - PHANINDRA, PURANDHAR TUMKUR (Digital Repository of Theses - SSBM Geneva, 2023)
Risk is an integral part of any project and it's more appropriate to say for IT Industry because it is changing with a very fast pace. Different surveys, reports and research show astonishing statistics about the risks in projects of IT Industry. Through proper risk assessment techniques most of the uncertainties can be reduced while initiating, implementing, and improving IT projects. Different authors talk about different risks and different strategies to respond to them. It becomes difficult at times to keep in check all the risks. Often risk management is over hyped, and often it's totally neglected. Their needs to be a balanced approached in risk management. The aim of this research project is to develop and analyze a structured approach using Artificial Intelligence which will help organization in identifying & categorizing risks and measuring their impact on projects in IT Industry well in advance.